2014
DOI: 10.1188/14.onf.117-125
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Promoting Physical Activity Among Cancer Survivors: Literature Review and Epidemiologic Examination

Abstract: Nurses are encouraged to promote physical activity in cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…[5][6][7][8][9] There is also emerging evidence that exercise can reduce recurrence and mortality in some cancer populations. [10][11][12][13][14][15][16] Despite these benefits of exercise, there is a lack of evidence on the safety and efficacy of exercise in relation to dose. 6,17 The ideal mode and intensity of exercise for people with cancer is unclear, and exercise guidelines are based largely on expert clinical opinion and adaptations of guidelines for healthy people.…”
Section: Introductionmentioning
confidence: 97%
“…[5][6][7][8][9] There is also emerging evidence that exercise can reduce recurrence and mortality in some cancer populations. [10][11][12][13][14][15][16] Despite these benefits of exercise, there is a lack of evidence on the safety and efficacy of exercise in relation to dose. 6,17 The ideal mode and intensity of exercise for people with cancer is unclear, and exercise guidelines are based largely on expert clinical opinion and adaptations of guidelines for healthy people.…”
Section: Introductionmentioning
confidence: 97%
“…10 Thus it may become even more beneficial to survivors to exercise after treatment than it was pre-diagnosis. For example, cardio-pulmonary gains from exercise are especially significant for survivors who have undergone chemotherapy and may be at risk for cardio-pulmonary toxicities and aerobic capacity decline.…”
mentioning
confidence: 99%
“…In addition, several reviews and meta‐analyses have demonstrated that physical activity is associated with a lower risk of death, all‐cause mortality, and cancer recurrence, particularly among breast and colorectal cancer survivors 18 20 . Physical activity also reduces other comorbid chronic diseases such as type 2 diabetes and cardiovascular disease 11 , 21 . Despite this evidence, it is estimated that <10% of cancer survivors will be active during treatments and only 20%−30% will be active after treatments 22 , 23 .…”
mentioning
confidence: 99%